Intensity Distribution of the 31P¬11S+ Band System of NaLi - Sau, Vu Ngoc; Khoa, Dinh Xuan; Bang, Nguyen Huy (Communications in Physics, 2012)
In the framework of adiabatic approximation we perform numerical calculations of intensity distribution for the 31P¬11S+ band system of NaLi based on the Franck-Condon (FC) principle. In addition, the internuclear distances at which the most favorable transitions occurred are predicted.  Comparing the calculated FC factors and the corresponding spectral lines observed recently reveals a good agreement, particularly, at node of envelop of the FC factors. Some local deviations in spectral intensity between the calculated results and experimental data indicate local perturbations in the 31P state. This result requires further investigations in details.